Improving Student Outcome through Flexibility in Teaching and Evaluation Methods - Brintha, N. C.; Ebenezer, G.; Francis Saviour Devaraj, A.; Sivapragasam, C.; Winowlin Jappes, J. T. (Journal of Engineering Education Transformations, 2021)
As engineering education is becoming easily accessible, many students from diversified background are getting enrolled i.e., from different regions/states where their educational policies adopted during their school education is different. Bringing these diversified students to cope up, build their higher order skills to analyse and inculcate creativity, flexibility in teaching and evaluation is required. Although many institutions are given autonomy to design their courses and curriculum, when it comes to implement in classroom teaching, still the conventional mode of teaching and evaluation dominates the educational system. The outcome of autonomous learning was evaluated through a detailed survey taken from 265 students for python programming course and its outcomes are compared with conventional practices. While using conventional practice, students were not able to analyse and devise solutions to problems independently. They were not able to transform and apply the learnt concepts for real time applications and their learning outcome was found to be 52%. This mode of teaching has enhanced the higher order thinking skills, creativity, imagination, problem solving and conceptual understanding of our students. This paper realizes the advantages of autonomous courses by evaluating the results received from various evaluation surveys for ‘Python Programming’ autonomous course with students and teachers.